Destination brand authenticity to destination brand engagement in tourism destination - Sakti, Intan Widuri; Zakiah Darajat; Yori Rismayanti (Technium Social Sciences Journal, 2024)
This study examines Destination Brand Engagement (DBE) in the context of tourism primarily focusing on its outcomes rather than its antecedents. This study differs from previous studies in examines the impact of destination-centric drivers and tourist-centric perspectives. Specifically, this study explores how destination brand experience and destination brand authenticity (DBA) influence DBE. The results obtained from 352 tourists as sample and tested using structural equation modeling techniques revealed that destination brand experience and DBA positively and significantly influence DBE, along with discussions of significant managerial and theoretical implications.